Experimental study on damping properties of rubber powder modified styrene-acrylic emulsion concrete beam. (November 2020) - Mo, Jinxu; Zeng, Lei; Guo, Fan; Liu, Yanhua; Ma, Linling; Chen, Buqing; Liu, Xianpan
Abstract: In this paper, 4.5% rubber powder is added to improve the damping properties of styrene-acrylic emulsion concrete. A total of 66 specimens were manufactured, including eleven groups of prisms and cantilever beam specimens. Through the axial compression test of the prism specimen, the basic mechanical properties of rubber powder modified styrene-acrylic emulsion concrete were studied, and the interface morphology of rubber powder modified styrene-acrylic emulsion concrete was observed by scanning electron microscope (SEM). After the cantilever beam specimen is damaged in different degree, a free vibration test is conducted. The damping properties of beams at various damage stages are discussed. Experimental results show that the addition of styrene-acrylic emulsion enhances the toughness and damping capacity of concrete by about 20.4%, but reduces the compressive strength by about 36%. Meanwhile, when the amount of styrene-acrylic emulsion is increased, it can slow down the rate of cantilever beam stiffness degradation. Rubber powder reduces the compressive strength by about 21.4% and accelerates the degradation of dynamic stiffness while enhancing the damping capacity of concrete by about 20.4%. Through SEM observation, it is found that there are many holes on the surface of cement stone after rubber powder falls off, which is the main reason for the decline in mechanical performance after rubber powder falls off. The nonlinear relationship between the displacement angle and the damage index is established by statistical analysis. Highlights: The rubber powder is added into the SAEC beams as damping unit. Axial compression and free vibration tests were carried out on different specimens. Damping properties of SAEC beams modified by rubber powder were quantified. Damage damping capacity, stiffness degradation and energy dissipation quantified.